Expansion tube capabilities for studying boost-glide re-entry conditions - Lin, Y; Wallington, JJ; James, CM; Bui, T; van den Herik, TJ; Chang, EWK; Hermann, TA (Springer, 2025)
The expansion tube is a unique hypersonic impulse facility capable of producing both high-enthalpy and high total pressure conditions simultaneously through the unsteady expansion of a non-stagnated test flow. When coupled with highperformance free-piston or detonation drivers, expansion tubes allow for the simulation of such conditions as scaled Earth re-entry, scaled entry into the atmospheres of other planets in the solar system, and high-speed flight through the Earth’s atmosphere. This paper focuses on the latter case and considers the capabilities of expansion tubes for re-creating the conditions experienced at various parts of the re-entry trajectory of a boost-glide vehicle. Boost-glide vehicles are a type of hypersonic vehicle which is generally boosted just outside the atmosphere by a rocket before ‘gliding’ down through the Earth’s atmosphere to a target, often re-entering at very high-speeds for atmospheric flight of up to Mach 22 (greater than 6 km/s). In a military sense, they are strategically important and are currently being developed by several nations around the world. The expansion tube’s unique ability to simulate high-enthalpy and high total pressure flight makes it particularly well suited to the study of these conditions. This paper will present expansion tube performance envelopes compared to planned boostglide trajectories, as well as considering specific facility considerations required to generate these conditions.